2014
DOI: 10.1097/cad.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and molecular mechanisms underlying the antileukemic activity of the histone deacetylase inhibitor belinostat in human acute promyelocytic leukemia cells

Abstract: Therapeutic strategies targeting histone deacetylase (HDAC) inhibition have become promising in many human malignancies. Belinostat (PXD101) is a hydroxamate-type HDAC inhibitor tested in phase I and II clinical trials in solid tumors and hematological cancers. However, little is known about the use of belinostat for differentiation therapy against acute myelogenous leukemia. Here, we characterize the antileukemia activity of belinostat as a single drug and in combination with all-trans-retinoic acid (RA) in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 40 publications
(45 reference statements)
3
24
0
Order By: Relevance
“…A preclinical study of belinostat in three hepatocellular carcinoma cell lines (PLC/PRF/5, Hep3B and HepG2) showed that it can inhibit cell growth in a dose dependent manner and induce histone acetylation in all three cell lines [ 63 ]. Antileukemia activity of this compound as a single drug and in combination with all- trans -retinoic acid was characterized in promyelocytic leukemia HL-60 and NB4 cell lines, where belinostat can exert dose-dependent growth inhibitory or proapoptotic effects promoting cell cycle arrest at the G0/G1 or the S transition phase [ 64 ].…”
Section: Fda Approved Drugsmentioning
confidence: 99%
“…A preclinical study of belinostat in three hepatocellular carcinoma cell lines (PLC/PRF/5, Hep3B and HepG2) showed that it can inhibit cell growth in a dose dependent manner and induce histone acetylation in all three cell lines [ 63 ]. Antileukemia activity of this compound as a single drug and in combination with all- trans -retinoic acid was characterized in promyelocytic leukemia HL-60 and NB4 cell lines, where belinostat can exert dose-dependent growth inhibitory or proapoptotic effects promoting cell cycle arrest at the G0/G1 or the S transition phase [ 64 ].…”
Section: Fda Approved Drugsmentioning
confidence: 99%
“…In addition, ChIP results indicated the obvious increase in hyperacetylated histone H4 association with p27 promoter region. It was demonstrated earlier 22 , that belinostat up-regulates NB4 cells p27 protein levels as well. Taken this data together, it is plausible not to underestimate the role of p27 activation in belinostat-mediated antileukaemic effect.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, our group previously indicated 22 that, although belinostat promotes APL granulocytic differentiation, as a single agent it has no effect on NB4 cells C/EBPα and C/EBPε genes expression or genes coding for transcription factors that drive granulocytic differentiation 47 , 48 . In this study, using ChIP, we aimed to determine histone H4 hyperacetylation level in C/EBPα and C/EBPε promoter regions.…”
Section: Discussionmentioning
confidence: 99%
“…These observations fueled a lot of investigations on the anticancer properties of AF and its analogues, and on the underlying molecular mechanisms [ 2 , 3 , 4 , 5 ]. In recent years, new knowledge regarding the molecular mechanisms involved in leukemia cells growth has shifted the focus of antileukemic drug development to agents acting on specific molecular targets and pathways that regulate signal transduction, epigenetic alterations, cell death, and cell cycle progression [ 6 , 7 , 8 , 9 ]. In this regard, the ubiquitin-proteasome system seems to be a particularly attractive target [ 10 ].…”
Section: Introductionmentioning
confidence: 99%